Determinants of manufacturing-R&D co-location - Mikko Ketokivi; Jyrki Ali-Yrkkö (The Research Institute of the Finnish Economy (ETLA), 2007)
The phenomenon of physical R&D-manufacturing co-location is interesting, because researchers have made very different observations regarding its prevalence. In some populations co-location of the two functions seems to be the norm; in others, an exception. However, we still do not have an explicit explanatory theory of co-location. In this paper, we look the reasons why manufacturing and R&D may have to be physically co-located. In a sample of 241 Finnish industrial firms, we find that the need for co-location varies drastically from company to company. We further find that product complexity, process complexity and industry clockspeed have an effect on co-location need.
Keywords: D21; D23; F21; F23; L6; O32; 330; Business location decisions; co-location; R&D; manufacturing; contingency theory; Betriebliche Standortwahl; Verarbeitendes Gewerbe; Industrielle Forschung; Kontingenztheorie; Finnland